Long-term outcome of anterior cruciate ligament reconstruction with an autologous four-strand semitendinosus tendon autograft - Streich, Nikolaus; Reichenbacher, Sebastian; Barié, Alexander; Buchner, Matthias; Schmitt, Holger (International orthopaedics, 2013)
Purpose Although the short- and mid-term outcomes of ACL reconstruction with a hamstring graft are promising, clinical investigations reporting the long-term results after ten years or longer are rare. Therefore we performed a retrospective single-blinded evaluation of ACL reconstruction using a four-stranded single-bundle reconstruction with a semitendinosus tendon graft with extracortical fixation. Methods/Results At follow-up patients obtained at least the same level in the clinical outcome scores (Lysholm, IKDC, Tegner) compared to previous studies with a similar follow-up time using a STG graft. Furthermore there was no detectable difference in the incidence of osteoarthritis. Patients having a negative pivot shift test showed significantly fewer signs of radiographic osteoarthritis and better functional assessment scores. Conclusion On the basis of our investigation, we conclude that the reconstruction of the ACL by a quadrupled semitendinosus tendon graft with extracortical anchorage can achieve excellent clinical and subjective results after a follow-up of ten years.